Production of Nata from Wastewater of Tofu (Whey): Study on Sucrose and Mungbean Sprout Extract Addition - Nisa, Fithri Choirun; H., Hani R.; Wastono, Tri; Baskoro, B.; Moestijanto, Moestijanto (Jurnal Teknologi Pertanian, 2001)
Nata, as the alternative high fiber food, was produced from coconut water and pineapple. Wastewater of tofu (whey), that became the environmental problem, has potency as the material of nata production.The objective of this study was making use of the tofu waste water (whey) potency as the alternative material to produce nata, by studying nutrition component addition, that was sucrose as carbon source and mungbean sprout extract as nitrogen source. The sucrose addition with five treatments, i.e. 0; 2,5; 5,0; 7,5; and 10,0 g / 200 whey and mungbean sprout extract addition with four treatments, i.e. 0; 0,1; 0,3; and 0,5 (ml / 200 ml whey), with incubation time 14 days, at temperature 28ï‚±3oC.The analysis was comprised of material analysis and product analysis. Material analysis included protein, carbohydrate, total solid content, and acidity analysis, and product analysis include weight and thickness of nata analysis. Results showed that the best product was obtained from sucrose and mungbean sprout extract addition 20 g / 200 ml whey and 0,5 ml / 200 ml whey, respectively, with 23,79 g weight and 6,5 mm thickness.Keywords: tofu wastewater, nata, fiber food